Монголчуудын "Нялхсыг ухияах" зан үйл: Боржгин тайж нарын гэрийн аман уламжлал - Г., Нандинбилиг (Mongolian Studies, 2023)
In this article, we will study of ritual for naming infants of the Boijgin nobility “taij nar”, based on the oral tradition about familial rituals and ceremony “infant bathing” of the “taij nar” in the main bag (the smallest administrative unit of Mongolia) of the former Dalai Choinkhor Vang khoshuu of Sain Noyon Khan province - the current Zurkh bag of Galt sum, Khuvsgul province. This familial ceremony originates from its ancient times and it has changed significantly, some of the detail have been lost, but the original concept has been preserved. So the main rituals and symbols have been studied, some forgotten information has been learned from historical sources and earlier studied Buryat traditions, Mongolian children’s cairn rituals and oral literature. The aim is to restore the literature works with examples of previously documented sutra of the big dipper (7 burhan) and the insurance and then the pray of the shaman.